Preoperative cystoscopy could determine the severity of placenta accreta spectrum disorders: An observational study. Issue 1 (23rd August 2018) - Al‐Khan, Abdulla; Guirguis, George; Zamudio, Stacy; Alvarez, Manuel; Martimucci, Kristina; Luke, Davlyn; Alvarez‐Perez, Jesus
Abstract: Aim: In the surgical treatment of placenta accreta spectrum disorders, cystoscopy for prophylactic stent placement is performed to protect the ureters from potential injury. Despite its frequent use, the use of cystoscopy in assessing the severity of these disorders has not been explored. Our objective was to find out if the abnormal findings documented during cystoscopy are associated with disease severity. Methods: In this retrospective, observational cohort study ( n = 56), the bladder wall was evaluated at the time of ureteral stent placement via cystoscopy in prenatally diagnosed placenta accreta spectrum cases. Three abnormal findings were commonly present in these cases: bulging of the posterior bladder wall, neovascularization and arterial pulsatility in the area of neovascularization. These findings were stratified according to severity in histologically confirmed specimens. Continuous variables were compared via two‐tailed t‐tests and Wilcoxon rank sum tests. Categorical data were evaluated using logistic regression analysis. Results: Neovascularization affected 84%, bulging 71% and pulsatility 54% of the cases. Bulging and neovascularization increased with disease severity. Pulsatility occurred exclusively in percretas. Bulging was associated with a 12‐fold (OR = 11.6, 95% CI 2.94–46.33, P = 0.0005) increased likelihood of percreta and neovascularization with a 17‐fold (OR = 17.06, 95% CI 2.98–97.79, P = 0.0014) increase. Neovascularization and/or the presence of bulging of the bladder have high positive predictive value for placenta increta and percreta (91.5% and 95.0%, respectively). Cystoscopy can be used to assess the severity of placenta accreta spectrum cases preoperatively, especially when placentation is over the previous uterine scar and is in proximity to the bladder wall.